Reverse Colonialism: A Theoritical Inquiry into the Social Construction of the Filipino Community in Diaspora - Padilla, Efren N. (Silliman Journal, 2022)
This article is a theoretical inquiry on the unique and dynamic Filipino-American relation and its impact on the Filipino immigrant community in the United States. Specifically, it examines the social construction of Filipino-American community in the context of reversing the negative impact of American colonialism. In doing so, this article frames the question not in terms of what America has done to us, but what we have done or what we are doing despite America. The former represents the danger of looking at our identity as the by-product of victimization— a form of pathology that often requires the pills of entitlement to cure its symptoms. The latter, on the one hand, represents a departure from the pathology of victimization towards a reconstructed and recovering community. It is my hope that this essay will help us to confront the continuing legacies of American colonialism, as well as to better understand the dynamics of contemporary Filipino-American experience.